THE MODERATING ROLE OF WORK STRESS VARIABLES ON THE EFFECT OF WORKLOAD VARIABLES ON JOB SATISFACTION VARIABLES AT THE NATIONAL NARCOTICS AGENCY OF LUBUK LINGGAU CITY - Lia, Diah April; Sari, Tri Agriana; Rimbano, Dheo; Famalika, Ade (Jurnal Media Ekonomi (JURMEK), 2024)
This study aims to analyze the role of work stress moderation on the influence of workload on the job satisfaction of employees of the National Narcotics Agency (BNN) of Lubuklinggau City. We know that excessive workload can lead to a decrease in job satisfaction, which ultimately affects organizational performance. This study uses a quantitative research type approach with path analysis, the population involves ASN and TKS employees in the Lubuklinggau City BNN environment who are used as respondents.